Flavonoid, Nitrate and Glucosinolate Concentrations in Brassica Species Are Differentially Affected by Photosynthetically Active Radiation, Phosphate and Phosphite - Trejo-Téllez, Libia Iris; Estrada-Ortiz, Elías; Gómez-Merino, Fernando Carlos; Becker, Christine; Krumbein, Angelika; Schwarz, Dietmar (Frontiers in Plant Science, 2019)
We evaluated the effects of phosphate (Pi-deficiency: 0.1 mM; Pi-sufficiency: 0.5 mM), phosphite (low-Phi: 0.1 mM; medium-Phi: 0.5 mM; and high-Phi: 2.5 mM), and two mean daily photosynthetically active radiations (lower PAR: 22.2 mol·m-2·d-1; higher PAR: 29.7 mol·m-2·d-1), as well as their interactions, on flavonoid, nitrate and glucosinolate (GL) concentrations and growth characteristics in hydroponically grown Brassica campestris cv. Mibuna Early and Brassica juncea cv. Red Giant. As expected, higher PAR increased dry matter and contrariwise decreased number of leaves but only in B. campestris. Total flavonoid and individual flavonoid compounds increased with the higher PAR value in B. campestris. Pi-sufficiency resulted in a lower quercetin concentration in both species, the isorhamnetin and total flavonoid concentrations in B. campestris, and the cyanidin concentration in B. juncea, in comparison to Pi-deficiency. Similarly, Pi-sufficient plants exhibited lower GL concentration, especially alkyl-GLs in B. campestris and alkenyl-GLs and an aryl-GL in B. juncea. Pi did not affect the nitrate concentration in either species, and nor did Phi influence the flavonoid concentrations in either species. In B. campestris, medium Phi (0.5 mM) increased the 1-methoxyindol-3-ylmethyl GL concentration in 28.3%, as compared to that observed at low Phi. In B. juncea, high Phi level increased the but-3-enyl-GL concentration in 18.9%, in comparison to values recorded at medium Phi. B. campestris plants exposed to higher PAR increased total flavonoids concentration. In both Brassica species, higher PAR stimulated the alkyl-, alkenyl-, and indole-GLs. The interaction of lower PAR and increasing Phi significantly decreased flavonoid concentration in B. juncea, whereas increasing Phi at higher PAR increased such concentration in this species. The same combination reduced the concentration of 2-phenylethyl- and indol-3-ylmethyl-GL in B. juncea. The highest indol-3-ylmethyl-GL concentration was observed when Pi was deficient combined with medium Phi in B. juncea. Thus, PAR, Pi and Phi may modulate flavonoid, GL and nitrate concentrations in Brassica species, which may be a useful tool to improve the nutraceutical quality of these leafy vegetables if properly managed.